2018
DOI: 10.1016/j.colsurfb.2018.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled nanoformulation of methylprednisolone succinate with carboxylated block copolymer for local glucocorticoid therapy

Abstract: A new self-assembled formulation of methylprednisolone succinate (MPS) based on a carboxylated trifunctional block copolymer of ethylene oxide and propylene oxide (TBC-COOH) was developed. TBC-COOH and MPS associated spontaneously at increased concentrations in aqueous solutions to form almost monodisperse mixed micelles (TBC-COOH/MPS) with a hydrodynamic diameter of 19.6 nm, zeta potential of -27.8 mV and optimal weight ratio ∼1:6.3. Conditions for the effective formation of TBC-COOH/MPS were elucidated by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Moreover, the area under the curve (AUC) of RBC-MPSS-CSNPs group was 861.85 ng·h/mL, which was significantly higher than that of the MPSS-CSNPs group (334.32 ng/ml·h) and the MPSS injection group (281.78 ng/ml·h). The half-life of MPSS was approximately 0.5 h; therefore, the drug was unmeasurable shortly after the administration of MPSS injection [ 43 , 44 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the area under the curve (AUC) of RBC-MPSS-CSNPs group was 861.85 ng·h/mL, which was significantly higher than that of the MPSS-CSNPs group (334.32 ng/ml·h) and the MPSS injection group (281.78 ng/ml·h). The half-life of MPSS was approximately 0.5 h; therefore, the drug was unmeasurable shortly after the administration of MPSS injection [ 43 , 44 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Because the retention of a drug at the RW does not lead to a leveling of its concentration along the cochlear spiral (see also Plontke et al, 2007b), different strategies for drug delivery to the cochlear apex should be employed. Stable drug loaded nanocarriers (Zou et al, 2014; Li et al, 2017; Kamalov et al, 2018) which can stay in the ST long enough without being cleared into the surrounding tissue may be a feasible option. When the concentration of nanocarriers along the ST reaches a constant level, the encapsulated drug could be released from the carriers through thermal or light activation (Karimi et al, 2016, 2017; Yuan et al, 2017) to obtain sufficient drug concentrations along the entire cochlear spiral.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that the complex of TBC and MPS is able to undergo self-assembly to obtain uniform and relatively stable micelles, which are characterized by high encapsulation efficiency and cellular availability of MPS. The initial study of the preparation demonstrated increased cellular uptake and antiradical activity of the complex compared to free MPS [29]. These data confirmed the possible use of TBC/MPS as a pharmaceutical composition.…”
Section: Discussionmentioning
confidence: 53%
“…The most studied amphiphilic polymers include ethylene oxide (EO) and propylene oxide (PO) block polymers [26,27]. In the aqueous environment, amphiphilic triblock copolymers (TBC) can spontaneously fuse to form polymeric micelles [28,29]. The specific features of delivery systems based on nanomicelles are their small size and preservation of drug stability [30].…”
Section: Introductionmentioning
confidence: 99%